Productivity growth, human capital and distance to frontier in Sub-Saharan Africa - Michael Danquah; Osman Ouattara; Alan Speight (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2010)
Using the Malmquist productivity index and panel data methods, we study the role of total human capital and its composition in the technological "catch-up" process and productivity growth via the channels of innovation and adoption of technology in a panel of 19 sub -Saharan African countries between 1960 and 2003. Our findings indicate different roles played by the composition of human capital and a follow-on consistent and significant contribution of total human capital to productivity growth. Primary and secondary school attainment (unskilled labour) contribute significantly to the adoption of technology(the main source of productivity growth in sub-Saharan Africa) whilst tertiary school attainment (skilled labour) plays a significant role in local innovation. Total human capital on the other hand, contribute more significantly to the adoption of technology and innovation. Technological "catch-up" remains a significant element in productivity growth in sub-Saharan Africa and economies with higher tertiary school attainment(skilled labour) and higher total human capital tend to contribute significantly to productivity growth through the channel of technological "catch-up". Our results rather point towards a circuitous depiction of the symbiotic characteristics of the composition of human capital in enhancing productivity growth in sub-Saharan Africa and hence efforts in scaling- up investments in human capital by governments, development partners etc should not be too concentrated on one composition of human capital.
Keywords: D24; O47; O55; 330; Productivity growth; Human capital; Sub-Saharan Africa